2017
DOI: 10.1021/acs.jpca.7b08895
|View full text |Cite
|
Sign up to set email alerts
|

1,2-Fluorine Radical Rearrangements: Isomerization Events in Perfluorinated Radicals

Abstract: Devising effective degradation technologies for perfluoroalkyl substances (PFASs) is an active area of research, where the molecular mechanisms involving both oxidative and reductive pathways are still elusive. One commonly neglected pathway in PFAS degradation is fluorine atom migration in perfluoroalkyl radicals, which was largely assumed to be implausible because of the high C-F bond strength. Using density functional theory calculations, it was demonstrated that 1,2-F atom migrations are thermodynamically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 97 publications
1
15
0
Order By: Relevance
“…S4). 1,2-F radical rearrangement has been posited during the isomerization of perfluorinated radicals (69). However, in our case, density functional theory (DFT) calculations revealed that such a 1,2-F migration of Int-2 requires a high activation free energy (DG ‡ = 23.9 kcal/mol) and is endergonic by 12.1 kcal/ mol (fig.…”
Section: Mechanistic Studiesmentioning
confidence: 60%
“…S4). 1,2-F radical rearrangement has been posited during the isomerization of perfluorinated radicals (69). However, in our case, density functional theory (DFT) calculations revealed that such a 1,2-F migration of Int-2 requires a high activation free energy (DG ‡ = 23.9 kcal/mol) and is endergonic by 12.1 kcal/ mol (fig.…”
Section: Mechanistic Studiesmentioning
confidence: 60%
“…The mechanism of this unprecedent intermolecular fluorine atom transfer resulted from the C(sp 3 )–F bond cleavage is not yet fully understood, and it will be a subject of our further study. We cannot completely exclude possible formation of HF traces under the reaction conditions, which can potentially assist the fluorine transfer step . However, the observation of only compound C as a product of the fluorine elimination from PPFR is a clear evidence that fluorine anion is unlikely to be involved.…”
Section: Resultsmentioning
confidence: 91%
“… 7,15 Therefore, we calculated the PES scans of C4 to C6 RPFAs to evaluate their helical conformations and compare them against their PFA analogues. Probing helical conformations of RPFAs is more complex than PFAs, since RPFAs may undergo 1,2‐F atom shifts, causing the formation of more isomers of RPFAs 26 . For example, C4 RPFAs can have the chemical structures CF3CF2CF2normalĊnormalF2 and CF3CF2normalĊFCF3, which are referred as α‐C4RPFA and β‐C4RPFA (Figure S1, inset).…”
Section: Resultsmentioning
confidence: 99%
“…Probing helical conformations of RPFAs is more complex than PFAs, since RPFAs may undergo 1,2-F atom shifts, causing the formation of more isomers of RPFAs. 26 The most notable result of the PES scan of α-C4RPFA…”
Section: Conformational Distributions Of Radical Pfasmentioning
confidence: 99%